P PENETAPAN HARGA JUAL BELI LIMBAH KAYU PERSPEKTIF HUKUM EKONOMI SYARI’AH (Studi Kasus di CV. Kawan Kita Agung Mojoagung): SETTING PRICES FOR BUYING AND BUYING WOOD WASTE PERSPECTIVE OF SYARI'AH ECONOMIC LAW (Case Study on CV. Our Friend Agung Mojoagung) - Muhammad Irfan; Fitria, Norma (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2024)
This article the determination of buying and selling prices for wood waste on the CV Kawan Kita Agung Jombang from a sharia economic law perspective. Buying and selling activities carried out at our CV Kawan Kita Agung sometimes occurin gharrar, where when the ordered goods are delevired sometimes there are defect in quality, both from the CV seller of imbaj and the supplierwho sells product from recycled products, you should pay attention to the quality to the quality of the goods you are buying and selling so that they comply with the agreements and conditions made, so that there are no defects or horros in the buying and selling activities, and do not damage the greeting contract made. Keyword: buying and selling, greeting contract, ghoror